The stability research of complete hydraulic sections of mechanized roof support - Felonenko, S.V.; Gubkina, V.V. (Розробка родовищ, 2015)
Ways to improve the section sustainability of the complete mechanical hydraulic roof supports are analyzed. Theoretical and graphical relations of the stability margin sections for the complete roof supports in dependence with the extractive production angle while different motion schemes are obtained.